Girjjohallat girjáivuođa - Embracing Diversity - Drugge, Anna-Lill; Keskitalo, Pigga; Olsen, Torjer Andreas; Rahko-Ravantti, Rauna (Brill, 2025)
Unveil the dynamic world of Sami education across Finland, Norway, Sweden, and Russia in this book. This vital volume presents cutting-edge research from top scholars, enriching teacher education with innovative, interdisciplinary insights. Discover unique contributions through a blend of Sami and Māori perspectives, and navigate the profound impacts of history on modern educational challenges and Indigenous self-determination. Contributors are: Rauni Äärelä-Vihriälä, Kristina Belancic, Karianne Berg, Anna-Lill Drugge, Heidi Harju-Luukkainen, Máret J. Heatta, Hanna Helander, Huia Tomlins Jahnke, Ylva Jannok Nutti, Pigga Keskitalo, Asbjørn Kolberg, David Kroik, Marikaisa Laiti, Inker-Anni Linkola-Aikio, Torjer Olsen, Hanna Outakoski, Annika Pasanen, Rauna Rahko-Ravantti, Hilde Sollid, Tuija Turunen and Ekaterina Zmyvalova.